Finite element analysis of hot-mix asphalt layer interface bonding - Williamson, Matthew J. (Kansas State University, 2015)
Tack coat is a thin layer of asphaltic material used to bind a newly-placed lift of hot-mix asphalt (HMA) pavement to a previously-placed lift or a new HMA overlay/inlay and existing pavement. The purpose of a tack coat is to ensure that a proper bond occurs so that traffic loads are carried by the entire HMA structure. Proper bonding exists when HMA layers act as a monolithic structure, transferring loads from one layer to the next. This depends on appropriate selection of tack coat material type and application rate, and is essential to prevent slippage failure and premature cracking in the wearing surface. This study focuses on development of a three-dimensional finite element (FE) model of HMA pavement structure in order to assess HMA interface bonding. The FE model was constructed using commercially available ABAQUS software to simulate an Accelerated Pavement Testing (APT) experiment conducted at the Civil Infrastructure Systems Laboratory (CISL) at Kansas State University. Mechanistic responses measured in the CISL experiment, such as localized longitudinal strain at the interface, were used to calibrate the FE model. Once calibrated, the model was used to predict mechanistic responses of the pavement structure by varying the tack coat property to reflect material characteristics of each application. The FE models successfully predicted longitudinal strains that corresponded to APT results.
Keywords: Asphalt; Tack coat; Interface bonding; Finite element; Accelerated pavement testing; Civil Engineering (0543)